Optimalisasi Media Evaluasi Berbantuan Google Forms pada Mata Pelajaran Matematika - Subekti, Fitrianto Eko; Jazuli, Akhmad (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Training participants tend to already use Google Forms to create evaluation questions. However, its use is not optimal. To facilitate and solve partner problems, training was conducted on the use of Google Forms as an online evaluation medium by optimizing latex applications in creating questions containing mathematical equations. Activities are divided into three stages, namely preparation, implementation and evaluation. As many as 72.5% of participants attended to take part in training activities. Training participants gain knowledge, experience, and the opportunity to try using latex to create mathematical equations. The training activity received a positive response from the training participants. Participants were enthusiastic about taking part in the training and wanted follow-up activities with themes that were still related to the use of technology in learning.